Language Play Techniques in American Humorous Discourse (Based on Sitcom “Scrubs”) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article is devoted to the study of language game techniques in English language humorous discourse. The authors start with considering the notion of humorous discourse, which is viewed as text immersed in a situation of laughter. Incomplete components of humorous discourse are those of humorous tonality and humorous intention. Humorous intention is understood as an active position of the speaker, his or her desire to organize a humorous situation. Humorous tonality is treated as an emotional atmosphere of communication characterized by a friendly interrelationship of the participants in the conversation, as well as the mood of the interlocutors and their willingness to joke and laugh. These two components predetermined the choice of the factual material of the study, which is a popular American sitcom “Scrubs” (seasons 1, 4 and 8) telling about the life of physicians. The humorous effect of the sitcom is often created by the extensive use of language play. Language play is viewed in the study as a creative and non-standard (deviating from the norm) use of any language units and / or categories to create witty statements. In a broad sense, following L. Wittgenstein, who believed that any speech activity of a person is somehow related to language play, language play is understood as a certain type of the speaker’s speech behaviour based on a deliberate violation of systemic relations of language. To the characteristics of language play belong those of dialogism (presence of the addresser and addressee), creativity of speech activity, conjugation with a humorous effect and use of means of all language levels.The authors come to the conclusion that the characters of the American sitcom “Scrubs” use in their jokes almost all the language play techniques at all the levels of language structure: phonological (prosthesis, onomatopoeia, rhyme), morphological (contamination, suffixation, abbreviation), lexical (metaphor, epithet, hyperbole, pun, alogism, antonomasia, periphrasis, lexical repetition) and syntactic (syntactic repetition, rhetorical question, parcellation). In the sitcom, language play can be mostly found at lexical level (often-used are metaphors, epithets, hyperboles, comparisons, less often – alogisms and periphrases). Language play techniques are quite rarely found at phonological and morphological levels: for example, such technique as assonance has not been noted in the jokes of the sitcom characters. At syntactic level, the most commonly used technique of language play is repetition.
Keywords: Language Play; Language Play Technique; Humorous Discourse; Sitcom “Scrubs”; Humorous Effect; Language Level